Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Granular sludge-based partial denitrification/anammox achieving high anammox contribution for nitrogen removal from municipal wastewater using anoxic/aerobic process with independent sludge system - Ruixin Wu; Shenghao Ji; Chihao Lin; Haojie Qin; Min Ye; Yu-You Li; Jianyong Liu (Journal of Cleaner Production, 2026)

Widely targeted metabolomics of Salix songarica flowers: impact of drying methods on flavonoid profiles and antioxidant capacity - Xuemei Dai; Kaili Zhang; Zhuo Yao; Hao Li; Ruixin Lin; Wenwen Zhang; Yunhua Hu; Haixia Wang; Shangzhi Xu; Li Zhang (Food Bioscience, 2026)

A coupled hydro-mechanical model for zonal disintegration in deep tunnels based on strain gradient - Tianen Xue; Qiangyong Zhang; Kang Duan; Ruixin Zhang; Hanxiang Lin; Pengfei Wang (Computers and Geotechnics, 2025)

Dietary trehalose reduced liver glycogen accumulation and promoted protein deposition in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed a high-carbohydrate diet - Yi Xiao; Xingbo Su; Jiaying Xie; Huiwen Zhang; Qiming Huang; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Toxicity and Safety Assessment of Key Pesticides Used in Rice Fields on Rice Flower Carp (Procypris merus) - Qianxue Shao; Yongming Ruan; Ru Liang; Ruixin Jin; Zhixi Jin; Lin Xie; Yongqing Chi; Jiaojiao Xia; Pingyang Zhu (Fishes, 2025)
Integrated rice–fish farming, crucial for sustainable agriculture, relies on the judicious use of pesticide. This study evaluates the toxicity of six common rice-field pesticides on Procypris merus (rice flower carp), a key species in these systems. We conducted acute and chronic toxicity tests, assessing survival, growth, oxidative stress (SOD, CAT, MDA, 8-OHdG), and neurotoxicity (AChE). Results revealed a spectrum of toxicity: abamectin and trifloxystrobin were highly toxic; pretilachlor was moderately so; and glufosinate-ammonium, triflumezopyrim, and thiazole zinc were low. Notably, triflumezopyrim induced significant oxidative stress and DNA damage, while all three low-toxicity pesticides inhibited AChE activity, indicating potential neurotoxicity. Despite these effects, all observed toxicities were reversible within 7–14 days. Considering that the tested concentrations exceeded typical field application rates, glufosinate-ammonium, triflumezopyrim, and thiazole zinc are deemed relatively safe for P. merus at recommended dosages. Our findings provide critical insights for optimizing pesticide selection in rice–fish farming, balancing pest control with ecological safety, thereby informing sustainable agricultural practices.

Docosahexaenoic acid alleviated liver lipid deposition and health damage induced by cholesterol accumulation in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Qiming Huang; Huiwen Zhang; Xingbo Su; Yi Xiao; Jiaying Xie; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Development of Three Recombinase Polymerase Amplification Assays for the Rapid Visual Detection of Spiroplasma eriocheiris - Yunji Xiu; Ruixin Feng; Zongrui Yang; Lirong Jiang; Yiping Lin; Qingyue Xu; Dong Zheng; Shun Zhou (Journal of Fish Diseases, 2025)
Spiroplasma eriocheiris is a pathogen in the Chinese mitten crab Eriocheir sinensis and is associated with tremor disease. S. eriocheiris infects virtually all artificially bred crustaceans, resulting in significant economic losses to the aquaculture industry in China. Recombinase polymerase amplification (RPA) is considered a promising technology for the rapid and sensitive detection of disease. For the rapid detection of S. eriocheiris , this study established basic RPA, RPA‐EXO and RPA‐LFD, which were visualised via agarose gel electrophoresis, SYBR Green I, fluorescence signals and test lines on lateral flow dipsticks. Specific primers and probes were designed based on the 16S ribosomal RNA sequence of S. eriocheiris . The optimal primer pairs for the basic RPA, RPA‐EXO and RPA‐LFD were RPA‐F3/R3, RPA‐F3/R3 and RPA‐LFD‐F3/R3, respectively. The optimal temperatures and times of basic RPA, RPA‐EXO and RPA‐LFD were 37°C for 25 min, 39°C for 30 min and 39°C for 10 min, respectively. The specificity test indicated that in addition to the positive test results for S. eriocheiris , the other five DNA templates tested negative, demonstrating strong specificity. The results of the sensitivity test revealed that the detection limits of RPA, RPA‐EXO and RPA‐LFD were 5.77 × 10 −2 , 5.77 × 10 −4 and 1.52 × 10 −6 ng/μL, respectively, indicating high sensitivity. This study established three methods for the detection of S. eriocheiris that are characterised by a constant temperature, rapid response, high sensitivity and strong specificity.

LFN-YOLO: precision underwater small object detection via a lightweight reparameterized approach - Mingxin Liu; Yujie Wu; Ruixin Li; Cong Lin (Frontiers in Marine Science, 2025)
Underwater object detection plays a significant role in fisheries resource assessment and ecological environment protection. However, traditional underwater object detection methods struggle to achieve accurate detection in complex underwater environments with limited computational resources. This paper proposes a lightweight underwater object detection network called LightFusionNet-YOLO (LFN-YOLO). First, we introduce the reparameterization technique RepGhost to reduce the number of parameters while enhancing training and inference efficiency. This approach effectively minimizes precision loss even with a lightweight backbone network. Then, we replaced the standard depthwise convolution in the feature extraction network with SPD-Conv, which includes an additional pooling layer to mitigate detail loss. This modification effectively enhances the detection performance for small objects. Furthermore, We employed the Generalized Feature Pyramid Network (GFPN) for feature fusion in the network's neck, enhancing the network's adaptability to features of varying scales. Finally, we design a new detection head, CLLAHead, which reduces computational costs and strengthens the robustness of the model through cross-layer local attention. At the same time, the DFL loss function is introduced to reduce regression and classification errors. Experiments conducted on public datasets, including URPC, Brackish, and TrashCan, showed that the mAP@0.5 reached 74.1%, 97.5%, and 66.2%, respectively, with parameter sizes and computational complexities of 2.7M and 7.2 GFLOPs, and the model size is only 5.9 Mb. Compared to mainstream vision models, our model demonstrates superior performance. Additionally, deployment on the NVIDIA Jetson AGX Orin edge computing device confirms its high real-time performance and suitability for underwater applications, further showcasing the exceptional capabilities of LFN-YOLO.

Exploring advanced machine learning techniques for landslide susceptibility mapping in Yanchuan County, China - Wei Chen; Chao Guo; Fanghao Lin; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2024)

Protocatechuic acid enhanced Fe(III) activated peroxymonosulfate system for Sulfamethoxazole degradation in groundwater - Siqi Wang; Ran Wang; Qiutong Lin; Ruixin Liu; Xiaoyu Wu; Guangshan Zhang; Qi Hu; Zhao Jiang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Towards urban wind utilization: The spatial characteristics of wind energy in urban areas - Junliang Cao; Zhaoxing Chen; Shuai Kong; Lin Liu; Ruixin Wang (Journal of Cleaner Production, 2024)

Establishment and characterization of an intestinal epithelial cell line from Japanese flounder (Paralichthys olivaceus) - Lin Su; Baoshan Guo; Ruixin Feng; Yunfei Pang; Jiaxue Song; Shun Zhou; Yunji Xiu (Aquaculture, 2024)

Surface oxygenation of non-oxide boosts oxidation activity on polyoxometalate subunits: An enhanced Venus flytrap mechanism - Youwei Sun; Wenyu Long; Jian zhang; Yanjuan Wang; Shaozheng Hu; Yixin Lian; Weizhou Jiao; Ruixin Wang; Yazhou Zhang; Haiqiang Lin; Xinping Duan (Chemical Engineering Journal, 2023)

Monitoring and prediction of dust concentration in an open-pit mine using a deep-learning algorithm - Lin Li; Ruixin Zhang; Jiandong Sun; Qian He; Lingzhen Kong; Xin Liu (Journal of Environmental Health Science and Engineering, 2021)

Bioethanol production by heterologous expression of two individual 1-FEH genes from Helianthus tuberosus in Saccharomyces cerevisiae 6525 - Xi Zhang; Huanhuan Xu; Ruixin Fu; Lijin Jin; Haiyan Zhao; Lin Wang; Mingxiang Liang (BioEnergy Research, 2016)

A climatic dataset of ocean vertical turbulent mixing coefficient based on real energy sources - Yu Zhang; YiHua Lin; RuiXin Huang (Science China Earth Sciences, 2014)